On the Nature of Interplay among Major Flexibility Channels in Molecular Rotors - M. S. A. Abdel-Mottaleb (Journal of Chemistry)
As a part of our interest in the excited-state dynamics of flexible materials, we have undertaken a theoretical investigation to the photo-induced reactions of 2-[4-(dimethylamino)benzylidene]malononitrile (BMN) by a combination of the density functional theory, its extended time-dependent (TD-DFT) single reference, and ab initio molecular dynamic (MD) simulations. The results showed that double-bond twisting and the neighbor single-bond twisting togetherness in the excited singlet state is the most important nonradiative deactivation channel to the ground state. Double- and single-bond twisting insert clear intersections among the potential energy surfaces of the singlet states (especially S1/S0) leading to fluorescence quenching. Furthermore, effects of molecular dynamic simulations on molecular properties in the femtosecond to picosecond time domain are studied to validate the results. In agreement with the experimental results, the findings conclude the existence of a flexible geometry-dependent single emission band. Such a study may give information on how the molecule could be externally modified/fixed to yield a desired effect, i.e., more fluorescence or more nonradiative decay.